ANALISIS SPASIAL PEKERJA LANJUT USIA DI INDONESIA - Putricia Synthesa (Syiah Kuala University, 2020)
AbstractThe increasing number of elderly people in a country can be an indicator of the success of development carried out by the government because of the higher life expectancy in that country. However, the high percentage of the elderly population who are still working in Indonesia is interesting to discuss because more than 10 percent of elderly workers are unpaid workers. This study wants to see the mapping of the distribution of the elderly population as unpaid workers by province in Indonesia using spatial analysis and to see the variables that can affect the chances of an elderly person becoming unpaid workers using logistic regression analysis. The results of the study show that several provinces in Indonesia have a percentage of the elderly as unpaid workers above 15 percent. Of the 8 variables that were considered to affect the chances of the elderly to become unpaid workers, only 5 variables showed a statistically significant effect on the opportunities for the elderly to become unpaid workers. Elderly residents in blue-collar types of work have a 9.32 times higher chance of becoming unpaid workers than elderly people in white-collar types of work. The government needs to formulate appropriate policies in order to create conditions for the elderly population who continue to work but can receive wages and create a work environment that is friendly to the elderly who must continue to work.